Pengaruh Rebusan Air Daun Salam Terhadap Penurunan Tekanan Darah Penderita Hipertensi Pada Lansia di Desa Sampali - Sarumaha, Maslina; Sembiring, Hizkianta (Pustaka Galeri Mandiri, 2025)
As the number of elderly population increases, it has a complex impact. Various challenges caused by aging affect almost every aspect of life, including a decrease in the quality of life of the elderly. In addition, changes that occur in the elderly are changes in the body system that cause decreased function, making the elderly more susceptible to disease, especially degenerative diseases, one of which is hypertension. Objective to determine the effect of bay leaf boiled water on lowering blood pressure. Quantitative research method with pre-experimental design and using the one group pretest-posttest design method. The sampling technique used purposive sampling with 33 respondents. The analysis used was the Pairedt-test. The difference in blood pressure before (141/90) and after (129/84). The results of the study with the Paired t test on blood pressure before p value 0.001 (<0.005) and blood pressure after p value 0.001 (<0.005) indicate that there is an effect of boiled bay leaf water on reducing blood pressure in the elderly in Sampali Village, Deli Serdang Regency. There is a significant effect of boiled bay leaf water on reducing blood pressure in the elderly. For further researchers, it is recommended to be able to increase knowledge and additional information about giving boiled bay leaf water to lower blood pressure in hypertension sufferers.